Respuesta :

The expression that is equivalent to m(n(x)) is [tex]25x^{2} +90x+84[/tex].

It is given that

[tex]m(x) = x^{2} +3\\n(x) = 5x+9[/tex]

If there are two functions f(x) and g(x), how f g(x) will be calculated?

If there are two functions f(x) and g(x), f(g(x)) will be obtained by replacing x by g(x) into f(x).

So, [tex]m (n(x))= (5x+9)^2+ 3[/tex]

[tex]m (n(x))= 25x^{2} +81+90x +3[/tex]

[tex]m (n(x))= 25x^{2} +90x+84[/tex]

Therefore, the expression that is equivalent to m(n(x)) is [tex]25x^{2} +90x+84[/tex].

To get more about functions visit:

https://brainly.com/question/26613452

Answer:

b

Step-by-step explanation:

ACCESS MORE